2014
DOI: 10.1016/j.appet.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of parental pressure to eat and eating behaviours in preadolescents: The mediating role of anxiety

Abstract: Previous research suggests that parental controlling feeding practices are associated with children's over-eating and under-eating behaviours. However, there is limited research addressing the link between children's mental health symptoms (specifically anxiety and depression) and their reports of eating behaviours, despite knowledge that these psychopathologies often co-exist. The current study aimed to identify the relationships between preadolescents' perceptions of their parents' feeding practices with rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 66 publications
1
37
1
Order By: Relevance
“…Within influences currently included in the Birch and Davidson (2001) model, adolescent emotional eating was negatively associated with parental use of pressure. This finding was unexpected and is in contrast with previous cross-sectional research with adolescents which found a positive association between controlling feeding practices and increased pre-adolescent and adolescent disordered eating (Edmunds & Hill, 1999;Haycraft et al, 2014;Houldcroft et al, 2014;Loth, MacLehose, et al, 2014). Three of the studies finding this association used adolescent report of feeding practices, which measures their perception of controlling feeding practices (Edmunds & Hill, 1999;Haycraft et al, 2014;Houldcroft et al, 2014).…”
Section: Pressurecontrasting
confidence: 79%
See 2 more Smart Citations
“…Within influences currently included in the Birch and Davidson (2001) model, adolescent emotional eating was negatively associated with parental use of pressure. This finding was unexpected and is in contrast with previous cross-sectional research with adolescents which found a positive association between controlling feeding practices and increased pre-adolescent and adolescent disordered eating (Edmunds & Hill, 1999;Haycraft et al, 2014;Houldcroft et al, 2014;Loth, MacLehose, et al, 2014). Three of the studies finding this association used adolescent report of feeding practices, which measures their perception of controlling feeding practices (Edmunds & Hill, 1999;Haycraft et al, 2014;Houldcroft et al, 2014).…”
Section: Pressurecontrasting
confidence: 79%
“…When the children were pressured to eat, they tended to eat slower and avoid foods that their parents were pressuring them to eat (Powell et al, 2011). Higher parental use of pressure was also cross-sectionally associated with increased problematic eating patterns (e.g., dietary restraint, emotional eating) in a sample of children ages 7-10 years (Houldcroft et al, 2014).…”
Section: Impact Of Controlling Feeding Practicesmentioning
confidence: 94%
See 1 more Smart Citation
“…Parental pressure to eat is characterized by a tendency of parents to pressure the child to eat more, whereby parents directly influence what and how much their children eat (Birch et al, 2001). Parental pressure to eat is a common practice of parents' controlling the feeding of the younger child; however, parental pressure to eat has also been found to be associated with restrained, emotional and external eating in preadolescence (Houldcroft et al, 2014;van Strien & Bazelier, 2007).…”
mentioning
confidence: 99%
“…Nonetheless, despite the increasing interest in studying the impact of family functioning in the psychological adaptation of obese youths and on their weight (e.g., Blissett, Meyer, & Haycraft, 2011;Houldcroft, Farrow, & Haycraft, 2014;Washington, Rose, Colombo, Hong, & Coard, 2015), there has been little investigation regarding the sequential association between family environment, parents' adaptation and their child's adaptation (e.g., internalizing and externalizing symptoms). Moreover, the relationship between family and weight does not appear to be straightforward and the mechanisms that may account for this association remain unclear.…”
Section: Introductionmentioning
confidence: 99%